Crystallization and concentration modulated tunable upconversion luminescence of Er3+ doped PZT nanofibers. Issue 2 (20th November 2014) - Fu, Yike; Gong, Siyu; Liu, Xiaofeng; Xu, Gang; Ren, Zhaohui; Li, Xiang; Han, Gaorong
Abstract : Spectral tunable Er doped PZT nanofibers are fabricated by controlling crystallization and doping conditions using electrospinning for electro-mechano-optical microdevices. Abstract : Ferroelectric oxides with excellent electrical, mechanical and optical multifunctions play a vital role in future microdevices with diverse applications in energy, sensors and actuators. A series of Er doped PbZr0.52 Ti0.48 O3 (PZT:Er 3+ ) nanofibers with tunable upconversion photoluminescence (PL) properties were successfully synthesized via a sol–gel based electrospinning process. By controlled crystallization, PZT:Er 3+ nanofibers evolve from a polycrystalline to a single-crystalline-like structure, resulting in a remarkable increase in the visible upconversion emission intensity. It was uncovered that Er 3+ doping site in PZT shifts from B site to A site with increase in crystallinity and crystal size. In addition, remarkable enhancement in red emission is observed with increased Er 3+ doping concentration, which facilitates the modulation of emission colour from green to orange. Combined with the excellent ferroelectric properties of PZT, such spectral tunable PZT:Er 3+ nanofibers are considered as a promising multifunctional candidate for integrated electro-mechano-optical devices.